Hepatoprotective Activity of Ethanol Extract of Dewa Leaves (Gynura pseudochina (L.) DC) in White Rats (Rattus norvegicus) Induced by Paracetamol - Yelis Tria Monica; Listyawati, Shanti; Herawati, Elisa (Veterinary Biomedical and Clinical Journal, 2024)
The use of paracetamol in excessive doses can increase the hepatotoxicity effect, which causes acute hepatocellular injury. Dewa leaves (Gynura pseudochina (L.) DC) contain flavonoids, saponin, and tannin. This study aimed to determine the effect of ethanol extract from dewa leaves in reducing the impact of paracetamol induction on SGPT and SGOT levels and liver histology of white rats (Rattus norvegicus). The test was grouped into five treatment groups, namely: normal control; negative control with paracetamol induction 315mg/KgBW; Dewa leaf extract was administered with three variations in dosage, namely 3.15mg/KgBW, 3.50mg/KgBW and 3.85mg/KgBW and each treatment group consisted of 5 rats as replications. Dewa leaf extract was administered to the experimental animal, followed by the administration of paracetamol 8 hours after the extract was given orally; both treatments were given for 14 days. Measurement of SGPT and SGOT levels uses the photometric method. The hepatoprotective effect was further verified by histopathology of the liver. Liver histology was made using the paraffin method. SGPT levels, SGOT levels, and Hepatocyte Damage Scores were analyzed using Analysis of Variance (ANOVA); if the results are significant, continue with the Least Significance Difference (LSD) test at a significance level of 5%. The results of this study show that the administration of dewa leaf extract was not able to significantly reduce SGPT and SGOT levels in rats. The administration of dewa leaf extract at doses of 3.50mg/KgBW and 3.85mg/KgBW significantly prevented histological damage to rat livers.